2017
DOI: 10.1111/jvim.15028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Calcitriol Administration on Serum Ionized Calcium Concentrations after Parathyroidectomy: 78 Cases (2005–2015)

Abstract: BackgroundProphylactic administration of calcitriol has been suggested to mitigate the risk of hypocalcemia after parathyroidectomy. The effect of calcitriol on postoperative serum ionized calcium concentrations has not been evaluated in dogs after parathyroidectomy.Hypothesis/ObjectivesTo determine the effect of prophylactic calcitriol administration on postoperative serum ionized calcium (iCa) concentrations in dogs with primary hyperthyroidism (PHPTH) treated by parathyroidectomy.AnimalsSeventy‐eight dogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 30 publications
3
19
3
Order By: Relevance
“…Two studies found that dogs with higher preoperative serum tCa concentrations were not predisposed to hypocalcemia, which is consistent with our results . Authors of a recent article describing a study of dogs that were surgically treated for PHPT reported that prophylactic preoperative calcitriol administration was not associated with postoperative iCa or its rate of decrease after parathyroidectomy . The effect of prophylactic preoperative calcitriol administration on postoperative iCa in cats remains unknown.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Two studies found that dogs with higher preoperative serum tCa concentrations were not predisposed to hypocalcemia, which is consistent with our results . Authors of a recent article describing a study of dogs that were surgically treated for PHPT reported that prophylactic preoperative calcitriol administration was not associated with postoperative iCa or its rate of decrease after parathyroidectomy . The effect of prophylactic preoperative calcitriol administration on postoperative iCa in cats remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Median surgical time was relatively short (37 minutes). Similarly to dogs with PHPT, most (62.5%) cats were diagnosed with a parathyroid adenoma . However, parathyroid carcinoma was diagnosed in 21.9% of cats, which is higher than that reported in dogs (0%–15%) .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Primary hyperparathyroidism (PHPT) is a well‐recognized cause of hypercalcemia in dogs 1 . Despite this, research surrounding PHPT remains contentious 1–15 . In PHPT, a hypercalcemic state is produced through the secretion of parathyroid hormone (PTH) by pathologic chief cells (adenoma, hyperplasia, or adenocarcinoma) resulting in stimulation of renal tubular and intestinal calcium resorption and osteoclast‐mediated bone resorption 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also supports this theory, confirming the presence of a moderate correlation between the pre-operative iCa 2+ value and post-operative hypocalcemia [12]. Conversely, other authors report that the prophylactic administration of vitamin D has no protective value [20] and it should be limited to patients presenting signs of hypocalcemia or a severe decrease in serum calcium concentration after the procedure [21,22]. In the present study, a pre-operative supplementation was performed in only two (2/8) dogs.…”
Section: Discussionmentioning
confidence: 61%